Early predictors of successful military careers among West Point cadets. Issue 6 (1st November 2020) - Spain, Everett S.; Lin, Eric; Young, Lissa V.
ABSTRACT: The importance of leadership to organizational performance puts a premium on identifying future leaders. Early prediction of high-potential talent enables organizations to marshal scarce developmental resources and opportunities to those who are best positioned to show distinction in elevated roles. Much of the existing literature indicates that general mental ability remains the strongest predictor of future professional performance. Using data from 13 classes of West Point graduates who stayed in the Army to be considered for at least early promotion to the rank of major ( N = 5, 505), regression analyses indicate that cadet military grade point average surpasses both cognitive ability and academic performance by a considerable margin in the ability to predict future professional outcomes such as selection for early promotion or battalion command. Moreover, these differences in predicting managerial career outcomes endure over 16 years. Both practical and theoretical implications are discussed.